2007
DOI: 10.1080/10934520701750421
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of TCE-contaminated groundwater by a permeable reactive barrier filled with plant mulch (Biowall)

Abstract: A pilot-scale permeable reactive barrier filled with plant mulch was installed at Altus Air Force Base in Oklahoma, USA to treat trichloroethylene (TCE) contamination in groundwater emanating from a landfill. The barrier was constructed in June 2002. It was 139 meters long, 7 meters deep, and 0.5 meters wide. The barrier is also called a Biowall because one of the mechanisms for removal of TCE is anaerobic biodegradation. This study aimed at evaluating the performance of the pilot-scale Biowall after its insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Laboratory and field studies show that the plant mulch is a long‐term carbon source to sustain both biotic and abiotic transformation of TCE in the biowall (Kennedy and Everett ; Shen and Wilson ; Shen et al ). The performance of the biowall in attenuating TCE was presented in another paper (Lu et al ), and the monitoring data demonstrate that TCE concentrations were greatly reduced within the biowall, but increased again in the wells immediately downgradient of the biowall. This rebound in TCE concentrations downgradient of the biowall is not well understood, making it difficult to evaluate the remedial performance of the biowall objectively.…”
Section: Introductionmentioning
confidence: 91%
“…Laboratory and field studies show that the plant mulch is a long‐term carbon source to sustain both biotic and abiotic transformation of TCE in the biowall (Kennedy and Everett ; Shen and Wilson ; Shen et al ). The performance of the biowall in attenuating TCE was presented in another paper (Lu et al ), and the monitoring data demonstrate that TCE concentrations were greatly reduced within the biowall, but increased again in the wells immediately downgradient of the biowall. This rebound in TCE concentrations downgradient of the biowall is not well understood, making it difficult to evaluate the remedial performance of the biowall objectively.…”
Section: Introductionmentioning
confidence: 91%
“…The inclusion of the additional monitoring groundwater wells has been invaluable for determining background analyte concentrations and will be a crucial component for high-quality, long-term data analysis in subsequent years as evidenced elsewhere (FRTR Federal Remediation Technologies Roundtable (2003), Groundwater Services, Inc. 2004, Lu et al 2008, Gilbert et al 2013.…”
Section: Changes To the Biowall Designmentioning
confidence: 99%
“…In addition, the long‐term sustainability of biowall performance was identified as a key regulatory issue by AFCEE () and others (ITRC ; Obiri‐Nyarko et al ). Lu et al () demonstrated field performance at the OU‐1 biowall at Altus Air Force Base (AFB) based on 4 years of monitoring data. Longer term predictions of biowall longevity have typically been based on laboratory studies rather than field data collected from actual biowall sites.…”
Section: Introductionmentioning
confidence: 99%
“…Biowalls have been installed at two areas of the Altus AFB complex: at Operable Unit 1 (OU‐1) and at Spill Site 17 (SS‐17). The OU‐1 biowall was installed in the eastern portion of the base in June 2002 and has been the subject of several field and laboratory studies (Kennedy and Everett ; Lu et al ; He et al ; USEPA ; Lebrón et al ; Shen et al ; Whiting et al ). One focus of this prior research at the OU‐1 biowall was evaluating the potential for abiotic reactions.…”
Section: Introductionmentioning
confidence: 99%